PENGARUH KESEHATAN DAN KESELAMATAN KERJA (K3) DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN PT KINO INDONESIA, Tbk CABANG PRIGEN PASURUAN - Sistya Ernawaty; N. Rachma; Alfian Budi Primanto (UNIVERSITAS ISLAM MALANG, 2020)
ABSTRACT This study aims to determine the effect of 1) work safety and work discipline together or simultaneously on employee performance 2) occupational health and safety on employee performance and 3) work discipline on employee performance. The type of research in the preparation of this paper is research (explanatory research). The population in this study means the employees of PT Kino Indonesia, Tbk, Prigen Pasuruan Branch as many as 326 employees, with a sample size of 77 employees with data analysis techniques using multiple linear regression analysis. Based on the results of research and discussion that has been done, conclusions can be drawn, namely 1) Occupational and occupational safety (K3) and work discipline together or simultaneously have a significant effect on employee performance 2) Occupational and work safety (K3) has a significant influence on employee performance and 3) work discipline has a significant effect on employee performance. Keywords: Occupational Health, Work Safety (K3), Work Discipline and Employee Performance